Effect of subcutaneous tissue depth on outcomes of kidney transplantation. Issue 2 (4th March 2021) - Ruiz, Richard; Cox, Thomas; McKenna, Gregory J.; Onaca, Nicholas; Testa, Giuliano; Fernandez, Hoylan; Bayer, Johanna; Wall, Anji; Martinez, Eric; Gupta, Amar; DiNubila, J. Michelle; Jennings, Nicole; et al.
Abstract: Although post–kidney transplant (KT) wound complications are associated with elevated body mass index (BMI), BMI is not an accurate surrogate of obesity. On the other hand, subcutaneous depth (SQD) measurement is a direct marker of truncal obesity. We examined outcomes of differing intraoperative SQD measurements in 113 KT-only recipients over 20 months. Recipients' median age was 51 years; median BMI, 28 kg/m 2 ; and mean SQD, 2.9 cm. Patients were stratified into groups of SQD ≤2.5 cm, >2.5–5 cm, and >5 cm. An SQD of >2.5 to 5 cm correlated with a BMI of 30 kg/m 2 (obesity) and an SQD >5 cm correlated with a BMI >35 kg/m 2 (severe obesity). Degree of SQD was not associated with more frequent technical complications such as fascial dehiscence, lymphocele formation, renal artery thrombosis/stenosis, urine leak, or ureteral stenosis. However, an SQD >2.5 cm was a risk factor for requiring a wound vacuum-assisted closure device. There was no difference in graft or patient survival among the three SQD groups. Obesity, as measured directly by SQD, was not associated with increased technical complications or poor outcomes after KT. As expected, there was a higher incidence of wound complications in the higher SQD groups requiring intervention.